Answer:
![1 \frac{1}{6}](https://tex.z-dn.net/?f=1%20%5Cfrac%7B1%7D%7B6%7D)
Step-by-step explanation:
![\frac{3}{4}+ \frac{5}{12} =?\\](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D%2B%20%5Cfrac%7B5%7D%7B12%7D%20%3D%3F%5C%5C)
The fractions have unlike denominators. First, find the Least Common Denominator and rewrite the fractions with the common denominator.
×
+
×![\frac{1}{1})=?](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B1%7D%29%3D%3F)
Complete the multiplication and the equation becomes
![\frac{9}{12} + \frac{5}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B12%7D%20%2B%20%5Cfrac%7B5%7D%7B12%7D)
The two fractions now have like denominators so you can add the numerators.
![\frac{9+5}{12} = \frac{14}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B9%2B5%7D%7B12%7D%20%3D%20%5Cfrac%7B14%7D%7B12%7D)
This fraction can be reduced by dividing both the numerator and denominator by the Greatest Common Factor of 14 and 12 using
GCF(14,12) = 2
14÷2 / 12÷2 =7/6
The fraction
7/6
is the same as
7÷6
Convert to a mixed number using
long division for 7 ÷ 6 = 1R1, so
7/6= ![1 \frac{1}{6}](https://tex.z-dn.net/?f=1%20%5Cfrac%7B1%7D%7B6%7D)
Therefore:
3/4 − (−5/12) = ![1 \frac{1}{6}](https://tex.z-dn.net/?f=1%20%5Cfrac%7B1%7D%7B6%7D)
Solution by Formulas
Apply the fractions formula for subtraction, to
3/4 − (−5/12)
and solve
(3×12) − (−5×4) 4×12
=3/6− (−20/48)
=56/48
Reduce by dividing both the numerator and denominator by the Greatest Common Factor GCF( 56,48) = 8
56÷8 / 48÷8 =7/6
Convert to a mixed number using
long division for 7 ÷ 6 = 1R1, so
7/6= ![1 \frac{1}{6}](https://tex.z-dn.net/?f=1%20%5Cfrac%7B1%7D%7B6%7D)
Therefore:
3/4 − (-5/12) = ![1 \frac{1}{6}](https://tex.z-dn.net/?f=1%20%5Cfrac%7B1%7D%7B6%7D)
Answer:
392
Step-by-step explanation:
7(8) + 3(8)(14)
56 + 336
=392
*Brackets mean to multiply.
Part A: first multiply 2 by x and -3, then combine the like terms, after that add 6 from both sides, then subtract 6x from both side, the answer is -5.
4x + 2(x-3) = 4x + 2x - 11
4x +2x -6 = 4x + 2x - 11
6x -6 = 6x - 11
6x = 6x -11 +6
6x = 6x -5
6x-6x= -5
0 = -5
part B) add the like terms
Answer:
40/7
Step-by-step explanation:
14x - 71 = 9
14x=80
x=80/14
x=40/7
Answer:
3.33 or 3
Step-by-step explanation:
10 divided by 3 = 3.33 (it goes on) Or maybe you can't pour a third of a cup so maybe 3 or 4.